Magic by the book - Bernstein, Nina, 1949-; Kulikov, Boris, 1966- (New York : Farrar, Straus and Giroux, 2005)
After returning from a trip to the library, eleven-year-old Anne and her younger brother and sister discover a magic book which sends them on adventures in which they meet Robin Hood, giant bugs, and a dark, sinister man with a wolfish face.
"Frances Foster books."
Keywords: Magic -- Fiction; Space and time -- Fiction; Characters in literature -- Fiction; Books and reading -- Fiction; Brothers and sisters -- Fiction; Robin Hood (Legendary character) -- Fiction; Insects -- Fiction; Werewolves -- Fiction